Justice administration based on indigenous law in the Miskito community of Karata, North Atlantic Coast of Nicaragua - Rojas Hooker, Sandra Carolina (Universitetet i Tromsø, 2008)
This thesis discusses the Justice Administration System in Karata and the influence of Positive Law over the Indigenous Law or vice versa. The research was based primarily on participatory observation, focus group discussion, interviews with key person and literature review regarding Indigenous law, legal pluralism and conflict resolution. The conclusions reached was that Justice Administration in Karata is carried out by an administrative body composed by the Wihta, Elders, Communal Police, Religious Leader and Director from the Primary School, with the responsibility to maintain peace and social harmony in the community by the use of sanctions and punishment based on their customs and traditions such as public shame, talamana – payment of blood and exile. The Indigenous System of Law has experienced transformations that are evidenced during the oral hearing by the incorporation of elements from the Positive System of Law such as the principles of orality, immediacy and publicity among others, that requires the Wihta to have basic legal knowledge, due to the coordination/collaboration existing between authorities of the Indigenous system and the Positive System of Law. In relation to the knowledge and understanding of the Indigenous System of Law and the Positive System, the community members are aware of the existence of the Positive Law and have basic knowledge of the Human Rights instrument. Yet, the members of the community prefer the Indigenous System of Law and use the Positive System as a last resort when they claim that their standard Human Rights have been violated in the Indigenous System.